Pengembaangan Nilai-Nilai Pendidikan Kewarganegaraan Melalui Budaya Suba Jou (Salam Penghormatan) Pada Siswa SMA di Kota Ternate - Rustam Hasim; Jainudin Abdullah (Jurnal Geocivic, 2022)
This study discusses the development of civic education values through the suba jou culture for high school students in the city of Ternate. The background of this study explains that Salam Suba Jou is a form of sign communication that emphasizes the values, ethics and aesthetics of social relations in society. It is a traditional form of saluting by using both palms while bowing the head to an honored guest (leader) or an elder and/or older person. The practice of greeting Sub Jou itself in the life of the people of Ternate in general at Moloku Kie Raha is usually carried out more at traditional sultanate events. The habit of communicating with a handshake is more dominant than the Suba jou greeting. In terms of human values contained in Suba Jou culture, it is very universal and is not tied to certain ritual events. These values include mutual respect, mutual respect, mutual love, the value of unity and the value of togetherness. This is the reason for re-moving local cultural awareness together in the context of public communication by making Salam Suba Jou a tradition that is developed and preserved at the level of formal education, especially in high school in Ternate City.The Sultanate of Ternate has cultural diversity and unique exotic traditions in enriching the values of Citizenship Education. Ternate which consists of various tribes and local languages has inherited various forms of culture such as; art, dance, music, song and folk games. This diversity must be preserved and developed while maintaining noble values through educational media. This is in line with the objectives of Citizenship Education, which is to prepare students so that they have solid insight into their environment and attitudes and behaviors that are willing to preserve and develop natural resources, social quality. , and culture that supports national development as well as local development.The task of a Pancasila and Citizenship Education teacher is to instill character values into students which include components of knowledge, awareness or willingness and action to implement these values in everyday life. To develop their learning, a PPKn teacher must use local culture (Suba Jou) which is a culture that contains the values of the Ternate people which are used as guidelines for behaving in their daily lives. Strengthening local culture Civics education (Suba Jou) for students at Ternate City High School can be done in two stages, namely (1) integrating the preparation of learning implementation plans (RPP) in each subject with local wisdom that exists in the local community and (2 ) integrate the development of learning materials in each subject with local wisdom that exists in the local community.The objectives of this research are; (1), to find out the cultural values of Suba Jou which were developed in the subjects of Pancasila Education and High School Citizenship in Ternate City. (2). to find out the form of strengthening Pancasila and Citizenship education in the Suba Jou culture in high school students in Ternate City.This research is a field research or field research in which researchers go directly to the field to obtain data and information related to the research conducted. This research is presented in a descriptive form with the aim of describing the development of civic education values through the suba jou culture in high school students in the city of Ternate. Data collection in this study was carried out through several techniques, namely observation, interviews and documentation. The data analysis technique used by the researcher is by using three components of data analysis, namely, (1). Data reduction (data reduction). (2), Data Presentation (data display). (3), Drawing Conclusions/Verification (conclusion/drawing verification). In the final flow of this data analysis is drawing conclusions and verification. The conclusions put forward are final and permanent findings that can answer research problems.Kata Kunci: Budaya Lokal, Suba Jou, Nilai-nilai Kewarganegaraan.